Ultraviolet Laser Activation of Phosphorus‐Doped Polysilicon Layers for Crystalline Silicon Solar Cells - Yijun Wang; Di Yan; Jesus Ibarra Michel; Sanje Mahasivam; Vipul Bansal; Robert Delaney; Jiali Wang; Thien Truong; Peiting Zheng; Jie Yang; Xinyu Zhang; James Bullock (Advanced Materials Interfaces)
Abstract In crystalline silicon photovoltaics (c‐Si PV), a pulsed laser can be used as a substitute for a high‐temperature furnace dopant diffusion/activation step. In contrast to furnace‐based activation, lasers can be used to achieve highly localized doping with controlled dopant concentrations, useful in advanced architectures such as the interdigitated back contact (IBC) solar cell. In this study, a pulsed ultraviolet (UV) laser is utilized for phosphorus dopant activation within a low‐pressure chemical vapor deposited (LPCVD) polycrystalline silicon (poly‐Si) passivated contact layer. The highest implied open‐circuit voltage iVoc values achieved using this approach reach 726 mV. However, this comes at the expense of high specific contact resistivities ρc, which is attributed to a lower dopant concentration across the poly‐Si(n+)/SiOx/c‐Si interface. Regardless, the optimum iVoc, ρc combination is measured at a laser fluence of 0.78 J cm−2 producing values of 712 mV and 89 mΩ‐cm2, respectively. These values are still compatible with high‐efficiency solar cell designs, underscoring the feasibility and effectiveness of this approach.